Impact of therapeutic management and geriatric evaluation on patient of eighty years and older with diffuse large B‐cell lymphoma on survival: A systematic review. (21st September 2021) - Briand, Marguerite; Gerard, Stephane; Gauthier, Martin; Garric, Marie; Steinmeyer, Zara; Balardy, Laurent
Abstract: Background: Diffuse large B cell lymphoma (DLBCL) is an aggressive disease. The first‐line treatment is well defined in young patients; however, in oldest old patients treatment remains unclear. Objectives: To investigate the impact of therapeutics management and geriatric evaluation on survival in aged patients with DLBCL. Methods: We performed a systematic review of PubMed and COCHRANE databases of published report on elderly patients (median age 80 and above) with DLBCL, from January 2002 to January 2020. Results: We included 32 studies (6 prospective and 26 retrospective). Patients treated with anthracyclines‐containing chemoimmunotherapy had a 2‐year overall survival (OS) of 59%–74.3% in prospective studies and 48.1–64.6% in retrospective studies. With less intensive treatment without anthracyclines, 2‐year OS was 28%–53%. Without specific treatment, median OS was 2 months. History of falls and severe comorbidities were associated with a decreased survival. Conclusions: Chemoimmunotherapy with anthracyclines increases survival in selected very elderly patients in comparison with less intensive regimen. Geriatric assessment, in particular altered mobility disorders and severe comorbidities, is predictive of survival and should be associated with the therapeutic decision. More comparative studies are needed to guide the management of frailer patients.